The Effect of Information and Communication Technology on Poverty Reduction - Muhammad Ihsaan Rizqulloh; Muhamad Ferdy Firmansyah (International Journal of Engineering, Science and Information Technology, 2021)
Poverty is a problem that must be faced every year by the government. The government has made various efforts to overcome poverty. The field of information and communication technology has emerged as one of the factors that can influence poverty alleviation in this era of globalization. The development of information and communication technology in a country will impact the direction of people's behavior in various aspects. The development of information and communication technology has brought many changes for the better in human life worldwide. This study uses secondary data obtained from the Central Bureau of Statistics of Indonesia, the International    Telecommunications Union, and other relevant sources in this study. This study aims to determine and analyze the effect of information and communication technology on poverty alleviation with case studies conducted in 34 provinces in Indonesia. This study uses a quantitative descriptive method using panel data regression analysis method using the OLS (Ordinary Least Square) with Fixed Effect Model approach. The partial test (t statistical test) with a 95% confidence level shows that information and communication technology significantly affect poverty alleviation in 34 provinces in Indonesia. Therefore, in this case, the government needs to make efforts to increase the sub-index for the formation of the information and communication technology development index such as public infrastructure facilities in the information and communication technology sector as a means of supporting community activities, as well as community expertise in utilizing technology that the government can do to reduce poverty in 34 provinces in Indonesia.